Cerebral Palsy in relation to maternal health - Kisa Fatima; Altaf, Maria (International Journal of Endorsing Health Science Research, 2013)
Cerebral palsy (CP) is neurological disorder which effect motor and sensory neurons the effected individual may suffer ophthalmic problems, impaired speech, movements and posture mental and physical abnormalities as well. The study design was observational prospective, done on the population consists of 65 mothers having their child with CP, and children with other physical and mental disabilities were completely excluded. The data was collected at Dow Institute of Physical Medicine and Rehabilitation (IPM&R), DUHS. Prenatal causes (placenta previa, hypertension, diabetes, and seizures) accounted for majority of CP conditions. 21.5% mothers were found with gestational diabetes, 56.9% with hypertension, 16.9% with seizures and 20.0% with placenta previa.As it is well observed that Women with pregnancy induced diabetes (gestational diabetes) have a greater chance of having a baby with birth defects including CP. Gestational diabetes puts the fetus at greater risk of CP while women with hypertension are also most likely to have a child with CP.